2004
DOI: 10.1111/j.1085-9489.2004.09400.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous silent period in human immunodeficiency virus‐related peripheral neuropathy

Abstract: The aim of this work was first to determine whether the cutaneous silent period (CSP), a marker of small-nerve-fibre function, was altered in human immunodeficiency virus (HIV)-positive subjects with predominantly sensory symmetrical polyneuropathy and, second, to assess whether such alterations were predictive of an impairment in the largest calibre sensory and motor nerve fibres of the upper limb (UL) peripheral nerves. CSP was assessed in three groups of subjects: healthy control subjects, HIV-positive subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Painful stimulation, 10-15 times the perception threshold, produces action potentials in afferent nerves with conduction velocities of 15-20 m/s, which is similar to the Aδ fiber conduction velocity, resulting in development of a CSP by inhibition of alpha motor neurons [17,18]. Many clinical studies involving patients with peripheral neuropathies have shown abnormal findings in CSP measurements [19,20]. A study which assessed the CSP in 26 HIV-positive patients with polyneuropathies showed a significant delay in the latency of the CSP in all patients [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Painful stimulation, 10-15 times the perception threshold, produces action potentials in afferent nerves with conduction velocities of 15-20 m/s, which is similar to the Aδ fiber conduction velocity, resulting in development of a CSP by inhibition of alpha motor neurons [17,18]. Many clinical studies involving patients with peripheral neuropathies have shown abnormal findings in CSP measurements [19,20]. A study which assessed the CSP in 26 HIV-positive patients with polyneuropathies showed a significant delay in the latency of the CSP in all patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies involving patients with peripheral neuropathies have shown abnormal findings in CSP measurements [19,20]. A study which assessed the CSP in 26 HIV-positive patients with polyneuropathies showed a significant delay in the latency of the CSP in all patients [19]. An absent CSP was observed in patients with hereditary sensory autonomic neuropathies [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CSP might be useful in investigating the progression of neuropathy [45]. This technique needs validation in larger studies, however.…”
Section: Neurophysiologic Investigationsmentioning
confidence: 99%
“…Osio et al (2004Osio et al ( , 2006 suggest that a disorder of mitochondrial oxidative metabolism related to a reduction of mitochondrial DNA content and interference with nerve growth factor activity may be associated with DSPN. Interference with DNA synthesis and mitochondrial abnormalities produced by nucleoside ART have been hypothesized as pathogenic factors in ATN Recently, Herrmann et al (2006) reported that measures of small sensory fibers (leg epidermal nerve fiber density, cooling and heat pain thresholds) may be associated with transition to symptomatic HIV-associated distal sensory neuropathy 6 to 12 months later.…”
Section: Mitochondrial Toxicity and Dspnmentioning
confidence: 99%